2021
DOI: 10.1108/bjm-03-2020-0081
|View full text |Cite
|
Sign up to set email alerts
|

HPWSs and employee performance in KIBS companies: a mediating–moderating analysis

Abstract: PurposeThe purpose of this paper is to discuss relationships between high-performance work systems (HPWSs) and productive/counterproductive behaviours initiated and performed by employees. Using the ability, motivation and opportunities (AMO) theoretical framework, the authors described how an HPWS influences employee behaviours. The authors suggest that HPWSs could increase productive work behaviour and decrease counterproductive behaviours by mediating employees' affective commitment and moderating their sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…This suggestion is not surprising in the context of HRM research. Prior research has shown that the relationship between HRM practices and employee attitudes and behaviors can be moderated by a variety of factors including perceptions of leaders' behavior (Zhang et al, 2020), employee' self-efficacy (Wojtczuk-Turek & Turek, 2021), perceived procedural justice (Najam et al, 2020) and social relations -"wasta" (Alothmany, Jiang & Manoharan, 2022). In other words, while sustainable HRM offers individuals different HRM functions to enhance their job satisfaction, an employee's willingness to respond positively to those practices can depend on other variables.…”
Section: The Moderating Role Of Organizational Identificationmentioning
confidence: 99%
“…This suggestion is not surprising in the context of HRM research. Prior research has shown that the relationship between HRM practices and employee attitudes and behaviors can be moderated by a variety of factors including perceptions of leaders' behavior (Zhang et al, 2020), employee' self-efficacy (Wojtczuk-Turek & Turek, 2021), perceived procedural justice (Najam et al, 2020) and social relations -"wasta" (Alothmany, Jiang & Manoharan, 2022). In other words, while sustainable HRM offers individuals different HRM functions to enhance their job satisfaction, an employee's willingness to respond positively to those practices can depend on other variables.…”
Section: The Moderating Role Of Organizational Identificationmentioning
confidence: 99%
“…The traditional value of productivity is constantly diminishing, and relying on the crude growth mode has become unsustainable. To obtain long-term stable development, it is necessary to transition to innovative strategies [3][4]. Although in the key stage of economic transformation, but also can not be blind transformation; one needs to choose the way suitable for China's national conditions and the long-term development of China's enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…Lei Peng, Liang Qu and Yuanjie Xu. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] …”
mentioning
confidence: 99%